The Role of Stakeholders in HIA: A Landfill Site and Housing Development in Mundijong, Western Australia - Little, Marie; Earnest, Jaya; Spickett, Jeffery; Katscherian, Dianne (Australian Institute of Environmental Health, 2007)
The use of Health Impact Assessment (HIA) as a tool to identify and manage issues relating to health has not been widely adopted in Western Australia. Health Impact Assessment methodology was applied to two concurrent developments in the Shire of Serpentine Jarrahdale, Western Australia. Potential health impacts of the expansionof a sanitary landfill adjacent to a proposed housing development were identified following a literature review and stakeholder interviews. Recommendations to assess the risk to the community in the housing estate through quantitative analysis, and risk management strategies were provided to the Shire. The ability of an existing stakeholder group for the landfill, the South Cardup Landfill Stakeholder Consultative Group, to resolve concerns of the community relating to environmental and social issues were also evaluated. Recommendations to improve collaborative decision making were provided to the Stakeholder Group using the Framework for Democratic Science. The outcomes of the HIA informed the Shire of potential health impacts to assist decision making during the development application process and the design of a local District Structure Plan.